High density wave mapping to characterize low voltage substrate in sinus rhythm and atrial fibrillation: acute results from the WAVE-MAP AF study. (19th May 2022) - Starek, Z; Di Cori, A; Betts, T; Clerici, G; Gras, D; Lyan, E; Li, J; Hack, B; Zitella Verbick, L; Sommer, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Pulmonary vein isolation (PVI) is a recommended approach for all atrial fibrillation (AF) ablation procedures, but PVI alone does not cure all AF. Supplementary substrate modification beyond PVI has mixed results. Identifying low voltage zones and ablating those targets in addition to PVI may be beneficial. Electroanatomic mapping is critical to identify subjects that may require further substrate modification. The amount of low voltage area may be predictive of the optimal treatment approach. Purpose: This was a prospective, multicenter, interventional study of a high-density grid-style mapping catheter (HD Grid) to characterize left atrial (LA) low voltage substrate during sinus rhythm (SR) and AF in subjects undergoing de novo radiofrequency (RF) ablation for paroxysmal AF (PAF), early persistent AF (PsAF) (7 days-3 months) or non-early PsAF (>3 months-12 months) using a PVI only approach. Methods: High-density voltage maps were collected with HD Grid during both SR and AF prior to ablation. Differences in low voltage area between (1) SR and AF and (2) simultaneous orthogonal bipole wave configuration (HDW) and standard along-the-spline linear electrode configuration (SD) were investigated. Results: Three hundred subjects, enrolled at 18 centers in Europe and Israel, underwent PVI only RF ablation for PAF (N=113), early PsAF (N=79), and non-early PsAF (N=108). The average age was 62.0 ± 9.5 years and 70.3% (211/300) were male. SR maps and AF maps were available and evaluated in HDW and SD for 196 subjects (65.3%) (63 PAF, 65 early PsAF, 68 non-early PsAF). Mean LA surface area was 108.8 cm² and mean mapped surface area ranged from 83.2 to 89.5 cm². HDW maps showed less low voltage area compared to SD in all subgroups, both in AF and in SR (Figure). For example, in AF with a low voltage cutoff of 0.5 mV, mean low voltage area was 49.8 cm² using SD and only 45.6 cm² using HDW (p<.0001). Similarly, in SR with a low voltage cutoff of 0.5 mV, mean low voltage area was 16.1 cm² using SD and only 12.6 cm² using HDW (p<.0001). HDW showed significantly less low voltage area than SD in SR for all measured voltage cutoffs from 0.1 mV to 1.5 mV. On average, non-early PsAF subjects had a larger low voltage area than early PsAF subjects and PAF subjects in both SR and AF. In SR HDW, non-early PsAF subjects had 15.6 cm² under 0.5 mV, early PsAF subjects had 12.4 cm², and PAF subjects had 9.2 cm² (p=.0316). In AF HDW, non-early PsAF subjects had 56.6 cm² under 0.5 mV, early PsAF had 42.8 cm² and PAF subjects had 35.4 cm² (p<.0001). Conclusion: Non-early PsAF subjects had the largest low voltage area on average compared to both early PsAF and PAF subjects in this study. Using HD grid, HDW provided better low voltage area characterization compared to SD in both SR and AF. The final results of this study will suggest whether an HDW substrate characterization of low voltage area can predict recurrences after a single PVI-only strategy procedure.